2023
DOI: 10.3389/fped.2023.1093444
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome, doctor-patient relationship and family support of pediatric medical staff during a COVID-19 Local outbreak in Shanghai China: A cross-sectional survey study

Abstract: ObjectivesTo explore burnout syndrome (BOS) incidence, doctor-patient relationship, and family support on pediatric medical staff in Shanghai comprehensive hospitals during a COVID-19 local outbreak.MethodsA cross-sectional survey of pediatric medical staff from 7 comprehensive hospitals across Shanghai was conducted from March to July 2022. The survey included BOS, doctor-patient relationships, family support, and the related factors of COVID-19. The T-test, variance, the LSD-t test, Pearson's r correlation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Analyzing the timing, research indicates that the formation of the 2 peaks of the M-shaped pattern correlates with the outbreak in Shanghai in the first half of 2022 and the subsequent comprehensive relaxation of COVID-19 control measures in China toward the end of 2022. We have observed that these 2 incidents have caused varying degrees of strain on medical resources [ 40 ], while simultaneously leading to higher comment scores from patients toward hospitals. This finding aligns with previous research in this area [ 6 , 31 - 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the timing, research indicates that the formation of the 2 peaks of the M-shaped pattern correlates with the outbreak in Shanghai in the first half of 2022 and the subsequent comprehensive relaxation of COVID-19 control measures in China toward the end of 2022. We have observed that these 2 incidents have caused varying degrees of strain on medical resources [ 40 ], while simultaneously leading to higher comment scores from patients toward hospitals. This finding aligns with previous research in this area [ 6 , 31 - 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of organizations and decisionmakers, we recommend that they should focus on reducing workload, improving income policy while offering more social support for medical workers. On one hand, it is of great necessity to optimize the proper ow of personnel within the department, and alleviate the work intensity by reducing working hours 44 . On the other hand, social support can be improved through creating a good working atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no targeted antiviral medication that is advised for the treatment of COVID-19, a condition that has the potential to result in acute respiratory distress syndrome, multiple organ dysfunction syndrome, and fatality. The combined efforts of traditional medicines and conventional treatments have demonstrated a noteworthy reduction in mortality rates, a shortened duration of fever, a decrease in chest radiograph abnormalities, and relief from secondary fungal infections in patients undergoing glucocorticoid therapy for severe acute respiratory illnesses [1,2]. With these functions, the consumption of herbs and natural products increased significantly on a global level [3].…”
Section: Introductionmentioning
confidence: 99%